Evaluation of the CIPP Model for Integrated STEM Learning in STEM Institutions Based on the Mathematics Learning Processes and Outcomes - Agus Maqruf; Tatang Herman (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
This research was carried out at a STEM institution with a focus on evaluating the implementation of STEM Integrated learning. The aim of this research is to evaluate using the CIPP (Context, Input, Process, Product) model for STEM Integrated learning and assess students' learning achievements in the field of mathematics studies, as well as evaluate the effectiveness of the STEM Integrated learning process using the CIPP model in STEM institutions. The effectiveness of the learning process is assessed based on the level of achievement of learning objectives that have been set at the beginning of the learning period, namely in all aspects of STEM. This research adopts a qualitative approach using the CIPP model, which allows evaluation of aspects of context, input, process and product to achieve effective learning. Research participants involve students, STEM instructors. Primary data was collected through observation instruments, while secondary data was obtained from documentation and interviews. The results of the research show that the application of Integrated STEM learning in STEM-EC UPI can be categorized as good in the input component but can be categorized as quite good in the context, process and product components. This is due to the less than optimal mathematical aspects in the STEM Integrated approach in terms of instructor qualifications and aspect assessment results. mathematics students.